Una valutazione economica di citrato di fentanile ad assorbimento orale (Actiq®) per la terapia del dolore in pazienti affetti da cancro - Lucioni, C.; Mazzi, S. (Farmeconomia. Health Economics and Therapeutic Pathways, 2004)
Breakthrough cancer pain is a component of chronic cancer pain that is particularly difficult to treat due to its severity and rapid onset. Effective relief of cancer pain is an integral part of comprehensive cancer care. Many cancer patients experience persistent pain that is treated with a fixed scheduled opioid regimen. But these patients can experience acute breakthrough pain, with sudden onset that occurs spontaneously or as a result of activity. To supply this occurrence is indicated an addictional prescription of opioids. The ideal preparation for managing breakthrough pain is one that is able to mirror its characteristics, i.e. rapid in onset and relatively short in duration. Oral transmucosal fentanyl (Actiq®), an innovative form of fentanyl citrate, provides a rapid onset of pain relief and it is more appropriate than morphine for treating episodes of breakthrough pain. Besides the impact on the patients’ quality of life, cancer pain involves remarkable expenditures, as direct and indirect costs, by the National Health Care System and the Society. This study presents the estimation of the costs associated with the use of oral transmucosal fentanyl (Actiq®). Aim of the study is to verify if the use of oral transmucosal fentanyl (Actiq®) can be considered as cost saving or cost effective compared with current therapy.